Analisis Hambatan Praktik Aktivitas Fisik Pada Mahasiswa Kedokteran Dalam Mendukung Gerakan Masyarakat Hidup Sehat (GERMAS) - Heryudi Julianus Jovly Soelama; Angelheart Joy Maynard Rattu; Joudy Djouvy Abelin Robert Gessal (Sam Ratulangi Journal of Public Health, 2022)
Background: Physical activity is any form of body movement produced by skeletal muscles that releases energy. Lack of physical activity has been identified as the fourth leading cause of death globally (6% of global deaths). The purpose of this study is to analyze what are the barriers to the practice of physical activity in medical students in supporting GERMAS. Methods:This research was conducted using a qualitative method on medical students of the Faculty of Medicine, Unsrat Manado in 2020-2021, using a purposive sampling technique. The target population is all students at the Faculty of Medicine, Unsrat Manado and the affordable population in this study are representatives of students and leaders of the Faculty of Medicine, Unsrat Manado, who are informants. Informants in this study were based on the principles of appropriateness and adequacy. The informants in this study were 7 people consisting of the Dean of the Faculty of Medicine UNSRAT, Deputy Dean III of the Faculty of Medicine UNSRAT, Koas students and regular students. The instruments used are interview guide, note book, cellphone voice recorder, and cellphone camera. Data collected in this study through in-depth interviews and direct observation. Data analysis using content analysis. Results: The results showed that based on the results of in-depth interviews and document observations, the results that 1) The perception of medical students towards the practice of physical activity is not an obstacle, 2) The availability of time for medical students to practice physical activity to support GERMAS is an obstacle, 3) Institutional support in implementing programs that encourage medical students to do physical activity in support of GERMAS has only been carried out informally and has not been implemented formally.Conclusion: This research can be concluded that medical students encounter obstacles in practicing physical activity.